Impact of infection control interventions on rates of Staphylococcus aureus bacteraemia in National Health Service acute hospitals, East Midlands, UK, using interrupted time-series analysis - Newitt, S.; Myles, Puja R.; Birkin, J.A.; Maskell, V.; Slack, R.C.B.; Nguyen-Van-Tam, Jonathan; Szatkowski, Lisa (Elsevier, 2015)
Background: Reducing healthcare-associated infection (HCAI) is a UK national priority. Multiple national and regional interventions aimed at reduction have been implemented in National Health Service acute hospitals, but assessment of their effectiveness is methodologically challenging.